Key success factors of social services organizations in the public sector = Kluczowe czynniki sukcesu organizacji świadczących usługi socjalne w sektorze publicznym - Frąckiewicz-Wronka, Aldona; Szołtysek, Jacek; Kotas, Maria (Zielona Góra: Faculty of Economics and Management Press)
The basic goal behind any action undertaken in an organization management is the will to achieve success. Key (or critical) success factors are the organization's resources, competence and qualification that create its competitive advantage on a particular market at a given time, and are able to determine its possible future success. The aim of this article is to identify key success factors of the social service organizations in the public sector.
Keywords: kluczowe czynniki sukcesu; organizacja publiczna; usługi socjalne; key success factors strategy; public organization; social services